Gestão do processo de projeto de instalações elétricas em empreendimentos hospitalares - Breno de Assis Oliveira (2015)
This thesis concatenates several concepts through research in designmanagement process applied to the process of conception of electrical facilities designs, in the context of hospital projects. Two case studies related to relevant recently reformed hospital projects in Minas Gerais were developed. These studies, combined with a literature review which covered the situation of design management and its various disciplines involved, show an extensive framework of the difficulties found in the conception of electrical installations designs in hospital projects, its causes and possible actions to minimize the risks inherent in projectsthat, due to its nature, offer high level complexities and require full interaction between the various stakeholders. The lack of a proper briefing, the use of outdated management techniques and the technical unfamiliarity about the exposed specialties at hospital facilities cause strained relations between the stakeholders, and therefore: noncompliance with deadlines, disrespect to planned budgets, and gaps in conforming to expectations of investors, contractors and users of easily affected projects, considered essential equipment, even if publicsectoror nonpublic. Finally this study offers two contributions in an effort tominimizing the presented risks: in first place, a briefing for the conception of electrical installations designs in hospital projects; in second place, an electrical design sequence based on the latest design management techniques.